2015
DOI: 10.1175/jtech-d-14-00191.1
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Spectral Estimation of HF Radar Data for Current Measurement Applications

Abstract: This paper presents a comparative study of high-resolution methods for high-frequency radar current mapping. A z-domain transformation and auxiliary z-domain manipulation of the autoregressive method is proposed for this comparison. A Weibull distribution test is recommended to justify the Rayleigh distribution of the sea clutter for quality control. Upon the power spectrum estimation, a conventional centroid method and a new symmetric-peak-sum method for the identification of current Doppler shift are propose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Sea clutter is asymmetrically spread across Doppler zero, peaking at specific resonance frequencies with some smaller peaks at adjacent frequencies. Due to this pattern with frequent peaks irregularly scattered around the Doppler dimension, the overall distribution of sea echo is better represented by heavy-tailed distributions than the traditionally used Rayleigh, 4,5 such as Weibull, log-normal, Pareto, or K-distribution. [6][7][8] In particular, the Weibull distribution is a suitable choice for modeling of general radar clutter signals, and Bucciarelli 9 showed that a good performance can be obtained in this scenario.…”
Section: Introductionmentioning
confidence: 99%
“…Sea clutter is asymmetrically spread across Doppler zero, peaking at specific resonance frequencies with some smaller peaks at adjacent frequencies. Due to this pattern with frequent peaks irregularly scattered around the Doppler dimension, the overall distribution of sea echo is better represented by heavy-tailed distributions than the traditionally used Rayleigh, 4,5 such as Weibull, log-normal, Pareto, or K-distribution. [6][7][8] In particular, the Weibull distribution is a suitable choice for modeling of general radar clutter signals, and Bucciarelli 9 showed that a good performance can be obtained in this scenario.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the use of Autoregressive (AR) modeling was applied by [16] within the framework of iceberg detection in HFR coastal measurements. Later on, [17] first proposed an AR approach in the context of oceanographic HFR, whose interest has been confirmed through subsequent studies [18,19,20]. To date, however, these methods have been confined to specific applications and have not yet earned their letters of nobility in the common HFR signal processing toolbox.…”
Section: Introductionmentioning
confidence: 99%